2010
DOI: 10.26719/2010.16.10.1079
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of barbers about hepatitis B and C transmission in Hyderabad, Pakistan

Abstract: Hepatitis B and C virus (HBV/HCV) infections are serious global health problems. Shaving by barbers has been identified as the key risk factor for spread of HBV. We conducted a cross-sectional survey of barbers in Hyderabad city, Pakistan in 2007 to establish their knowledge and attitudes to the risk of HBV and HCV transmission and their working patterns. Observations showed that 96.2% washed razors with antiseptic after each client and 95.7% used a new blade with new clients. However, knowledge about the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 10 publications
9
34
3
2
Order By: Relevance
“…The practice of using a new blade for every customer was common, as reported, among 90% of the barbers. This finding is consistent with other studies and indicates a uniform improvement in the practices of barbers across different countries [2,17,21]. We did not perform a regression analysis due to an insufficient number of HBV cases.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The practice of using a new blade for every customer was common, as reported, among 90% of the barbers. This finding is consistent with other studies and indicates a uniform improvement in the practices of barbers across different countries [2,17,21]. We did not perform a regression analysis due to an insufficient number of HBV cases.…”
Section: Resultssupporting
confidence: 92%
“…The poor response could be attributed to the lack of knowledge about the preventive role of vaccine and its cost. Unlike in other studies [2,17] hand-washing after each shave or haircut was an uncommon practice and majority of the barbers did not report it as part of their routine. Hand-washing not only helps maintain self-hygiene but also reduces the risk of infection transmission to clients.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…This finding also compares with the observations of a previous report [14]. Regarding awareness about the quality of blade, most of the barbers and clients insisted on use of a new blade, a finding analogous to that of another study [15]. A recent study showed that about half of the barbers and one third of their clients knew about hepatitis but only a small percentage of them could identify it as a disease of the liver, and only 13% and 42% of the barbers and clients respectively had the knowledge that hepatitis can be transmitted by razors.…”
Section: Discussionsupporting
confidence: 86%